A Hiperleukositosis pada Pasien dengan Kanker Paru - Divian Ozaza Sari; Yusuf Aulia Rahman (CV. Jasa Sukses Abadi, 2021)
Leukocytosis can be found in patients with lung cancer at the time of diagnosis or during the course of the disease. Hyperleukocytosis was defined as a leukocyte count above 11.000/mL on pheripheral blood. This case report describes hyperleukocytosis in a paraneoplastic syndrome resulting from lung cancer in a 42-year-old man who has had fever and weakness since the last 3 months. Peripheral blood morphological examination, there is increased leukocyte, 88% segment neutrophils, no blast cell and negative BCR-ABL examination. In people with lung cancer, leukocytosis can be caused by infection, use of corticosteroid, hematopoietic disorders, bone marrow involvement, or paraneoplastic manifestations. Paraneoplastic leukocytosis is associated with poor prognosis and aggressive disease, so the diagnosis of hyperleukocytosis in paraneoplastic syndromes is important because it determines the patient's prognosis. Paraneoplastic syndrome is a symptom seen in certain malignancies and is not associated with direct cancer invasion and occurs in 7-15% of all patients with cancer. Solid tumors activate a variety of different systems, namely the endocrine, neurological, mucocutaneous, and hematological systems. Granulocyte Macrophage Colony Stimulating Factor (GM-CSF), Granulocyte Colony Stimulating Factor (G-CSF), interleukin (IL) -1, IL-6 and Tumor Necrosis Factor (TNF)-α have been implicated in paraneoplastic leukemoid reactions. Among these, G-CSF is the strongest cytokine that triggers hyperleukocytosis.